Prioritizing implementation solutions for the urban family physician policy in Iran: a multi-criteria decision-making study - Lida Shams; Mohammadreza Mobinizadeh; Taha Nasiri; Fatemeh Mohammadi (BMC Health Services Research)
Abstract Background Family physician program is one of the effective reforms of the health system in Iran, but despite the implementation of this program in rural areas and the passage of ten years since its implementation in two provinces of Fars and Mazandaran, its implementation has faced problems. The aim of this study is to identify and prioritize implementation solutions related to the challenges of the family physician program in Iran. Methods This is a qualitative study using semi-structured interviews with 22 snowball-sampled experts and managers of basic health insurers to extract problems and executive solutions through coding and data analysis using Atlas Ti software and content analysis in the first stage. The combined criteria were used to report qualitative studies (COREQ). In the second stage, the extracted executive solutions were ranked using multi-criteria decision-making (MADM) and a hybrid approach combining Shannon entropy with simple aggregation weighting (SAW). Results Main themes were identified, including financing, management, human resources, structure, culture building, payment mechanism information systems, monitoring & control, performance of insurance organisations, and implementation. Out of these, priority was given to the information system, along with 41 sub-themes prioritising comprehensive, community-oriented physician training. Conclusion The findings of the study provide remedies for the problems of the Iranian Urban Family Physician Programme at the executive level and in priority order, from the standpoint of the insurance organisations. Making crucial decisions entails handling matters relating to funding, administration, personnel, architecture, ethos, remuneration, IT systems, oversight, insurance organization output, and execution.